Ionizing radiation effect on metal–ferroelectric–insulator–semiconductor memory capacitors. (28th July 2015) - Yan, S A; Li, G; Zhao, W; Guo, H X; Xiong, Y; Tang, M H; Li, Z; Xiao, Y G; Zhang, W L; Lei, Z F; Zhou, Y C
Abstract: A theoretical model was developed to investigate the ionizing radiation effect on the electrical characteristics of metal–ferroelectric–insulator–semiconductor (MFIS) structure capacitors under exposure to radiation and under post-irradiation conditions. In this model, the radiation-induced degradation in the ferroelectric layer, oxide layer and silicon dioxide interface were considered, and the radiation effect of the silicon substrate was also taken into account to accommodate the dose rate effect. The modeling results showed that both the capacitance versus applied voltage ( C–V ) curves and the surface potential versus applied voltage ( Φ S(Si) – V ) curves shifted significantly and the memory window became worse with increasing total dose. Moreover, the derived results indicated that the symmetry of the polarization versus applied voltage ( P – V ) curves degraded with the increase in total dose, which may explain the phenomena of radiation-induced fatigue and imprint. These results can provide some insights into the estimation of the radiation-induced degradation of MFIS structure devices and may be integrated into electronic design automation (EDA) software for ionizing radiation effect simulation.